Quelques perspectives de la conjoncture au cours des prochaines années (revues et corrigées) - Rabeau, Yves (L'Actualité économique, 1983)
AbstractIn this paper, we examine some of the factors that will have a major effect onthe economic cycle in the next few years. In particular, the impact of deflation,energy prices, capital costs and government deficits on income and expendituresbehaviour is discussed.